Differences in occupational values, communication types, job satisfaction, and organisational commitment among clinical nurses across generations - Lee, Seul A.; Lee, Jungmin (Frontiers in Psychology, 2023)
Introduction: This study examined occupational values, communication types, job satisfaction, and organisational commitment among clinical nurses across generations. Methods: Participants were 159 clinical nurses. Data were collected from 1–15 August, 2022, using a self-reported questionnaire. Results: Statistically significant differences were observed across generations in terms of job satisfaction (F=3.492, p=0.03) and organisational commitment (F=4.371, p=0.01). However, there were no differences in occupational values (F=0.765, p=0.47) or communication types (F=1.744, p=0.18) among clinical nurses across generations. There was a moderate to strong positive correlation between job satisfaction and organisational commitment across all generations, and a moderate positive correlation between job satisfaction and occupational values among Generation Y and Z. Discussion: To improve the quality of nursing care, various intervention programs based on the generational gap among clinical nurses need to be developed, to reduce conflicts, and ultimately establishing the necessary systems through mutual understanding of education.